Emerging tourism markets [videorecording] - Video Education Australasia (Australia : Video Education Australasia, 2009)
Investigates four new tourism markets in Australia: adventure tourism, ecotourism, indigenous tourism and MICE (meetings, incentives, conferences and exhibitions)
Executive producer, Simon Garner
Keywords: Tourism -- Australia